2000
DOI: 10.1093/humrep/15.2.319
|View full text |Cite
|
Sign up to set email alerts
|

Experience with the elective transfer of two embryos under the conditions of the German embryo protection law: results of a retrospective data analysis of 2573 transfer cycles

Abstract: The German embryo protection law (Embryonenschutzgesetz, ESchG) does not allow embryo selection. Therefore, only as many oocytes at the pronuclear stage (PN), as are planned to be transferred, are allowed to be cultured. It is not known whether, under these conditions, it is possible to reduce the number of embryos for transfer without a corresponding reduction of the overall pregnancy rate (PR). We retrospectively analysed 2573 consecutive transfer cycles following either in-vitro fertilization (IVF) or IVF/i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 23 publications
0
21
1
8
Order By: Relevance
“…Many studies have confirmed this importance of the cytoplasmic halo, showing an increased implantation rate when the cytoplasmic halo is present in zygotes [12,[17][18][19][20][21]. However, our study failed to find any such association, most likely because most of the embryos evaluated here showed a normal cytoplasmic halo pattern.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Many studies have confirmed this importance of the cytoplasmic halo, showing an increased implantation rate when the cytoplasmic halo is present in zygotes [12,[17][18][19][20][21]. However, our study failed to find any such association, most likely because most of the embryos evaluated here showed a normal cytoplasmic halo pattern.…”
Section: Discussioncontrasting
confidence: 52%
“…However, several authors have reported different results regarding the prognostic value of each PN feature. Some studies have reported a strong association between the PN orientation [9][10][11] or the number and distribution of NPB [12][13][14][15][16] and the implantation potential; others have suggested that an increased chance of implantation exists when the cytoplasmic halo is present in zygotes [2,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the studies of gene expression profiles of CCs have reported a noninvasive method to predict oocyte and embryo competence (Assou et al 2010). Together with morphological evaluation, CC genes may serve as biomarkers of oocyte and embryo selection during the IVF process or might result in an oocyte selection tool for those who are obliged to select a limited number of oocytes for fertilization in countries where embryo cryopreservation is legally restricted (Ludwig et al 2000). Herein, for the first time, we have reported a significant alteration of gene expression in CCs isolated from mature oocytes and immature oocytes of PCOS patients under COS to identify molecular signatures in CCs that are associated with oocyte maturation or embryo development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown this to be effective in reducing the risk of multi-fetal gestation [24]. Current consensus deemed a transfer of large numbers of embryos to increase "success rates" per IVF cycle is not justifiable.…”
Section: Discussionmentioning
confidence: 99%